Firm Value: CSR Disclosure, Risk Management And Good Corporate Governance Dimensions - Muhamad Fahminuddin Rosyid; Erwin Saraswati; Abdul Ghofar (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of Corporate Social Responsibilty(CSR) disclosure and risk management on firm value with Good Corporate Governance(GCG) as a moderating variable. The research sample was conducted on mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period of 27 companies with a total of 120 observed data . The data were analyzed by panel data regression processed with Stata 15 software. The results showed that CSR disclosure had a negative effect on firm value. Meanwhile, risk management has no effect on firm value. Furthermore, GCG as a moderating variable, proven to be able to streng then the relationship of CSR disclosure to firm value. However, GCG cannot be a moderating variable between risk management and firm value. Financial performance and firm size proved unable to be control variables in relation to the effect of CSR and risk management on firm value. The limitation of this research is that it is limited to mining companies listed on the IDX so that it can give different results if carried out in different industries. This research can contribute to the accounting literature related to firm value, especially with regard to CSR disclosure, risk management and GCG in companies in Indonesia.